2019
DOI: 10.1101/772038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-trait random regression models increase genomic prediction accuracy for a temporal physiological trait derived from high-throughput phenotyping

Abstract: 29Random regression models (RRM) are used extensively for genomic inference and prediction 30 of time-valued traits in animal breeding, but only recently have been used in plant systems. 31 High-throughput phenotyping (HTP) platforms provide a powerful means to collect high- 32 dimensional phenotypes throughout the growing season for large populations. However, to 33 date, selection of an appropriate statistical genomic framework to integrate multiple temporal 34 traits for genomic prediction in plant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Under the field conditions of multienvironment trials, as in our study, the genetic contribution to the observed phenotypes is both variable and reduced due to environmental fluctuations. Regarding genetic correlation of phenotypes across days (Figure 4), Campbell et al (2018) and Baba et al (2020) observed the same trend that we did, where the highest correlations were observed between adjacent time points.…”
Section: Genetic Architecture Of Soybean Temporal Above-ground Biomasssupporting
confidence: 83%
See 1 more Smart Citation
“…Under the field conditions of multienvironment trials, as in our study, the genetic contribution to the observed phenotypes is both variable and reduced due to environmental fluctuations. Regarding genetic correlation of phenotypes across days (Figure 4), Campbell et al (2018) and Baba et al (2020) observed the same trend that we did, where the highest correlations were observed between adjacent time points.…”
Section: Genetic Architecture Of Soybean Temporal Above-ground Biomasssupporting
confidence: 83%
“…The genetic correlation between longitudinal soybean AGB and grain yield is currently being investigated. Given HTPP's power to simultaneously collect multiple temporal traits, multiple-trait RRM may be powerful tools for joint genomic prediction of multiple longitudinal traits (Oliveira et al, 2016;Baba et al, 2020;Moreira et al, 2020). Therefore, RRM and HTPP have a great potential to accelerate the rate of genetic gain in soybean breeding programs.…”
Section: Potential Of Genomic Selection To Improve Soybean Temporal Above-ground Biomassmentioning
confidence: 99%
“…Genomics-Assisted Breeding (GAB) methodologies encompass an array of stages including characterization of germplasm collections; mapping population development; genomic region identification through association or genetic mapping; and application of molecular markers [24,25]. GAB rose to popularity in the field of plant breeding in the past few years partly due to the presence of low-cost NGS and highthroughput genotyping (HTPG) technologies [25] which allowed the rapid identification of superior genes implicated in climate resilience [26,3]. The fight against climate change needs immediate responses to counter the associated negative effects on crop productivity.…”
Section: Genomics-assisted Breeding (Gab)mentioning
confidence: 99%